Responsible Leadership for Multinational Enterprises in Bottom of Pyramid Countries: The Knowledge of Local Managers - Berger, Ron; Choi, Chong Ju; Kim, Jai Boem (2011)
The gulf between multinational enterprises’ focus on high income countries and the reality of 80% of the world living in developing, bottom of pyramid (Hahn, J Bus Ethics 84:313–324, 2009) economies could magnify the anti-globalisation movement and political backlashes in the twenty-first century. The global financial crisis of 2008 and 2009 has increased such social tensions throughout the world and creates greater challenges for, responsible leadership. In this conceptual article, the authors analyse the value and identity of local managers, and the liability of foreignness caused by over-reliance on expatriate managers and under-reliance on local managers in bottom of pyramid countries (Hahn, 2009). It is argued that multinational enterprises need to assess local managers’ knowledge and contributions as having not only operational and market value, but also institutional value, such as access to local knowledge and local social capital; such a holistic approach will ensure fairer, equal treatment of all managers in the multinational enterprise. Responsible leadership in the twenty-first century requires a greater appreciation of local managers’ institutional value and the overcoming of any psychological distance towards local managers of bottom of pyramid countries.
Keywords: Knowledge; bottom of pyramid; Psychic distance; Institutions; Liability of foreignness; anti-globalisation; Responsible Leadership